Distribution network planning considering technology diffusion dynamics and spatial net-load behavior. (March 2019) - Heymann, Fabian; Silva, João; Miranda, Vladimiro; Melo, Joel; Soares, Filipe Joel; Padilha-Feltrin, Antonio
Highlights: A model that exploits high resolution census data to spatially forecast technology diffusion patterns. A comparison of optimal distribution network expansion plans retrieved by state-of-the-art and spatially differentiated DER technology diffusion forecasts. A novel inference routine that applies Mutual Information to census data, unveiling the driving factors behind technology adoption. Abstract: This paper presents a data-driven spatial net-load forecasting model that is applied to the distribution network expansion problem. The model uses population census data with Information Theory-based Feature Selection to predict spatial adoption patterns of residential electric vehicle chargers and photovoltaic modules. Results are high-resolution maps (0.02 km 2 ) that allow distribution network planners to forecast asymmetric changes in load patterns and assess resulting impacts on installed HV/MV substation transformers in distribution systems. A risk analysis routine identifies the investment that minimizes the maximum regret function for a 15-year planning horizon. One of the outcomes from this study shows that traditional approaches to allocate distributed energy resources in distribution networks underestimate the impact of adopting EV and PV on the grid. The comparison of different allocation methods with the presented diffusion model suggests that using conventional approaches might result in strong underinvestment in capacity expansion during early uptake and overinvestment in later diffusion stages.